Combination strategy of laccase pretreatment and rhamnolipid addition enhance ethanol production in simultaneous saccharification and fermentation of corn stover. (February 2022) - Li, Huanan; Xiao, Wenjing; Liu, Jiashu; Ran, Qiuping; Wang, Rui; Yu, Cairong; Zhang, Xinyuan; Song, Huiting; Jiang, Zhengbing
Graphical abstract: Highlights: A novel environment-friendly ethanol production method was established. Combination strategy of laccase and rhamnolipid is effective in SSF of corn straw. The ethanol yields of combination strategy is 2.32 folds higher than corn stover. Rhamnolipid reduce non-production adsorption of cellulase to lignin. Laccase pretreatment break the resistance barrier of corn straw. Abstract: The effects of laccase pretreatment and surfactant addition in the simultaneous saccharification and fermentation (SSF) of corn stover by engineered Saccharomyces cerevisiae were studied. Surfactants Tween-80, tea saponin and rhamnolipid improved ethanol production in SSF, among which the biosurfactant rhamnolipid reached the highest ethanol yield. At the 6 d in SSF, the ethanol content of addition rhamnolipid of laccase pretreatment corn stover (Lac-CS) and Lac-CS reached 0.73 g/L and 0.56 g/L, which was 2.32 folds and 1.54 folds higher than the control of 0.22 g/L, respectively. These findings suggested that the combination of laccase pretreatment and rhamnolipid addition further improve ethanol production. GC–MS, composition of corn stover, protein concentration of supernatant and glucose content studies were executed to explore the mechanism of combination strategy of laccase pretreatment and rhamnolipid addition enhance ethanol production. This study provides guidance for the application of laccase and surfactant in bioethanol production.